Design and implementation of a graphene–polyimide-based H-slot terahertz antenna for wireless and biomedical applications - K. V. Vineetha; M. Siva Kumar; B. Sada Siva Rao; Om Prakash Kumar; Sudha Rani V; B. T. P. Madhav (PLoS ONE, 2025)
THz antennas, which function at high speeds, frequencies, and data rates, were developed in response to the increased need for high-speed communication equipment. In this work, a MIMO antenna operating between 2.25 and 2.85 THz is built and optimised with partial ground. The designed antenna possesses H-shaped slots and circular rings over the patch to enhance the antenna performance. The proposed antenna states the isolation loss value of 50 dB across the operating frequency with a bandwidth of 0.6 THz. In the manuscript, two antennas were designed, the first one having only circular slots and the second one, in addition to the circular slots over the patch, also including H-slots. The antenna has the highest gain value of 8.9 dBi in the design. Optimising the design is performed using parametric optimisation and geometrical parameters. The suggested antenna measures 50 x 50 x 100 µm². The suggested antenna can be used for high-speed communications because of its high gain and operating frequency applicability. Antenna having a low Error Correlation Coefficient (ECC) value of 0.08, a high Diversity Gain (DG) value with minimum mutual coupling < -25dB, an optimum Total Active Reflection Coefficient (TARC) value of -55dB and a Mean Effective Gain (MEG) value of 8.5dB. These antennae also operate across biomedical imaging applications, wireless network applications, beam scanning applications, and satellite communication applications with reflection coefficient values < -25dB.This study supports UN SDG 9: Industry, Innovation and Infrastructure by advancing sustainable THz communication technologies, and contributes to SDG 3: Good Health and Well-Being through its biomedical imaging applications.